Social Media Addiction and Bedtime Procrastination in Students - Muhammad Febrian Akbar; Sarah Afifah (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
Now, the internet has become a lifestyle necessity and is considered the most important part of human life. The presence of the internet in modern society does not only have positive impacts, but also negative ones. The increase in online activity via the internet has actually created social problems such as addiction to social media. Many factors are caused by social media addiction, one of which is bedtime procrastination. This study aims to determine the relationship between social media addiction and bedtime procrastination in Muhammadiyah 2 Palembang high school students. The research hypothesis is that there is a relationship between social media addiction and bedtime procrastination in Muhammadiyah 2 Palembang high school students. This study uses a correlational quantitative approach. Research participants consisted of 130 students with a total sampling technique. This scale consists of 2 scales, namely the social media addiction scale (a=0.809) and the bedtime procrastination scale (a=0.821). Data analysis in this study used the help of the JASP (Jeffrey's Amazing Statistics Program) for windows program. The results of the study showed that there was a significant positive relationship between social media addiction and bedtime procrastination in Muhammadiyah 2 Palembang high school students with a coefficient value of 0.306 with a significance value (p <0.001). The higher the social media addiction, the higher the bedtime procrastination, conversely, the lower the social media addiction, the lower the bedtime procrastination.Kini, internet telah menjadi kebutuhan gaya hidup dan dianggap sebagai bagian terpenting dari kehidupan manusia. Kehadiran internet dalam masyarakat modern tidak hanya memberikan dampak yang positif, tetapi juga negatif. Meningkatnya aktivitas online melalui internet sebenarnya telah menimbulkan masalah sosial seperti kecanduan media sosial. Banyak faktor yang disebabkan oleh kecanduan media sosial, salah satunya yaitu menunda waktu tidur (bedtime procrastination). Penelitian ini bertujuan untuk mengetahui hubungan antara kecanduan media sosial dengan bedtime procrastination pada siswa SMA Muhammadiyah 2 Palembang. Hipotesis Penelitian yaitu ada hubungan antara kecanduan media sosial dengan bedtime procrastination pada siswa SMA Muhammadiyah 2 Palembang. Penelitian ini menggunakan pendekatan kuantitatif korelasional. Partisipan penelitian terdiri dari 130 siswa dengan teknik total sampling. Skala ini terdiri dari 2 skala, yaitu skala kecanduan media sosial (a=0,809) dan skala bedtime procrastination (a=0,821). Analisis data dalam penelitian ini menggunakan bantuan program JASP (Jeffrey’s Amazing Statistics Program) for windows. Hasil Penelitian menunjukkan bahwa terdapat hubungan positif signifikan antara kecanduan media sosial dengan bedtime procrastination pada siswa siswa SMA Muhammadiyah 2 Palembang dengan nilai koefisien 0,306 dengan nilai signifikansi (p<0,001). Semakin tinggi kecanduan media sosial akan semakin tinggi bedtime procrastination, sebaliknya semakin rendah kecanduan media sosial akan semakin rendah bedtime procrastination.